Serum micronutrients and prealbumin during development and recovery of chemotherapy‐induced peripheral neuropathy. Issue 3 (September 2016) - Velasco, Roser; Santos, Cristina; Soler, Gemma; Gil‐Gil, Miguel; Pernas, Sonia; Galan, Maica; Palmero, Ramon; Bruna, Jordi
Abstract: Chemotherapy‐induced peripheral neuropathy (CIPN) is a frequent adverse event. Nutritional status can become impaired in cancer patients, potentially contributing to neuropathy's evolution. Our aim was to evaluate serum micronutrients and prealbumin in a cohort of 113 solid‐cancer patients receiving platinum and taxane compounds during the development and recovery of neuropathy, up to 1 year after finishing treatment. CIPN was graded according to Total Neuropathy Score © and NCI.CTCv3 at T0 (baseline), T1 (1–3 months), and T12 (12 months) after chemotherapy. CIPN was classified as asymptomatic (< grade 2) or symptomatic (≥2). CIPN recovery was defined as ≥1 grade improvement at T12. Symptomatic CIPN developed in 52% of patients. Symptomatic patients presented a higher increase in TNSc (p < 0.001), in TNSr © (p < 0.001), and decrease in sural (p < 0.001) and radial nerve conduction (p < 0.001). No significant differences with any of the micronutrients were observed along T0‐T1 period between severity or chemotherapy groups. By T12, symptomatic patients without recovery had a decrease in vitamin E levels (p = 0.019) and prealbumin (p = 0.062) compared with those symptomatic that improved. A correlation between the variation of vitamin E and prealbumin at T0‐T1 (r = 0.626, p = 0.001) and T1‐T12 (r = 0.411, p = 0.06) was observed. After chemotherapy treatment, the improvement of patients displaying symptomatic neuropathy is related to vitamin E and prealbumin serum levels. Our results suggest that nutritional status can play a role in CIPN recovery.